Theoretical size at the onset of maturity and its density-dependent variability as an option in crustacean fisheries management. (12th March 2021) - da Silva Santana, Cesar Augusto; Lordan, Colm; Power, Anne Marie
Abstract: Theoretical size at the onset of maturity (TSOM) for female Norway lobster was estimated by a new methodology based on the probability distributions of mature individuals built on physiological maturity measures. Onset of maturity using TSOM varied from 18.4- to 33.7-mm carapace length for the Irish functional management units (FUs). These estimates showed a significant negative linear relationship ( R 2 = 0.60) with population density and a significant positive linear relationship with average size in females ( R 2 = 0.84). The size class at which 50% of the females are sexually mature ( L 50 ) was linked to the new TSOM metric by a significant positive linear relationship ( R 2 = 0.40). This set of linear relationships ultimately allowed TSOM and L 50 to be estimated without a requirement for maturity stages to be distinguished. As well as contributing to the stock assessment and management of Nephrops (e.g. in data-limited FUs) and its potential for the calibration of more routinely used estimates, TSOM might be applied in new species and meta-analyses where size of maturity data are scarce. This new metric also better-defines the maturity process since, taken together, TSOM, L 50, and smallest berried female represent sequential maturity events: (i) onset of maturity, (ii) 50% mature (from gonad staging), and (iii) berried females.